TLR3 Activation of Intratumoral CD103+ Dendritic Cells Modifies the Tumor Infiltrate Conferring Anti-tumor Immunity - Roselli, Emiliano; Araya, Paula; Núñez, Nicolás Gonzalo; Gatti, Gerardo; Graziano, Francesca; Sedlik, Christine; Benaroch, Philippe; Piaggio, Eliane; Maccioni, Mariana (Frontiers in Immunology, 2019)
An important challenge in cancer immunotherapy is to expand the number of patients that benefit from immune checkpoint inhibitors (CI), a fact that has been related to the pre-existence of an efficient antitumor immune response. Different strategies are being proposed to promote tumor immunity and to be used in combined therapies with CI. Recently, we reported that intratumoral administration of naked poly A:U, a dsRNA mimetic empirically used in early clinical trials with some success, delays tumor growth and prolongs mice survival in several murine cancer models. Here, we show that CD103+ cDC1 and, to a much lesser extent CD11b+ cDC2, are the only populations expressing TLR3 at the tumor site, and consequently could be potential targets of poly A:U. Upon poly A:U administration these cells become activated and elicit profound changes in the composition of the tumor immune infiltrate, switching the immune suppressive tumor environment to anti-tumor immunity. The sole administration of naked poly A:U promotes striking changes within the lymphoid compartment, with all the antitumoral parameters being enhanced: a higher frequency of CD8+ Granzyme B+ T cells, (lower Treg/CD8+ ratio) and an important expansion of tumor-antigen specific CD8+ T cells. Also, PD1/PDL1 showed an increased expression indicating that neutralization of this axis could be exploited in combination with poly A:U. Our results shed new light to promote further assays in this dsRNA mimetic to the clinical field